2014
DOI: 10.1021/ol503455r
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Construction of Pyrroloindolines via an in Situ Generated Magnesium Catalyst

Abstract: An asymmetric formal [3 + 2]-cycloaddition between meso-aziridines and C3-alkylindoles mediated by an in situ generated magnesium catalyst was developed for asymmetric construction of pyrroloindolines. A variety of pyrroloindolines could be obtained by employing commercial available ligands with the assistance of an easily prepared achiral ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…13 These combined properties have made aziridines invaluable for setting stereochemistry through ring opening reactions, 46 and for production of larger N-heterocycles, such as 1,2,4-triazines or pyrroloindolines, via ring expansion. 710 Justifiably, aziridination has been employed in the synthesis of pharmaceuticals and natural products. 4, 11, 12…”
mentioning
confidence: 99%
“…13 These combined properties have made aziridines invaluable for setting stereochemistry through ring opening reactions, 46 and for production of larger N-heterocycles, such as 1,2,4-triazines or pyrroloindolines, via ring expansion. 710 Justifiably, aziridination has been employed in the synthesis of pharmaceuticals and natural products. 4, 11, 12…”
mentioning
confidence: 99%
“…Concerning the scope of the nitrile imines, the best enantioselectivities were generally achieved with those derived from benzaldehyde (Ar 1 = Ph) employed a chiral magnesium catalyst in situ generated from MgBu 2 and quinine to promote p-xylene at 60°C in the presence of the achiral N,O-bidentate ligand 31 as an additive, the formal [3 + 2] cycloaddition between C3-alkylindoles 32 and meso-aziridine 33a. 27 As shown in Scheme 10, the process afforded the corresponding chiral pyrroloindolines 34 in moderate to good yields (19-81%), good to high diastereoselectivities (78->90% de) and high enantioselectivities (86-94% ee). The presence of substituents with different electronic nature located at the C4-, C5-, or C6-position of the C3-methylindole was tolerated, while a C7-substituted indole proved to be much less efficient (19% yield).…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 96%
“…The authors found that employing N,O-bidentate ligands, such as picolinate, as non-covalent additives, could obviously improve the ee of the resulting pyrroloindolines. 96 The introduced second ligand could coordinate to the magnesium center to modify the chiral environment of the in-situ-formed catalyst, improving the results of the [3 + 2] cycloaddition reaction. It was also observed that other ligands with strong coordination abilities could improve the enantioselectivity.…”
Section: Additives' Effects (Second Ligand) In the In Situ Magnesium Catalysismentioning
confidence: 99%